Análisis de los mecanismos de cohesión en cuatro conversaciones en Facebook - Pérez Retana, David (2015)
This article presents the results of the research Mechanisms of Textual Cohesion in Conversations on Facebook, prepared to qualify for the mas- ter degree in Linguistics from the University of Costa Rica. Specifically, it analyzes how the mechanisms of textual cohesion interact in four con- versations in Facebook to determine how cohesion is achieved in such texts, and how it impacts on the thematic changes. For this purpose, four different conversations are discussed in detail. Such conversations include the four main mechanisms of cohesion available in Spanish: con- nection, reference, ellipsis, and lexical cohesion. The study shows the existence of textual mechanisms specialized in linking different inter- ventions into one conversation, while others mechanisms are oriented to linking textual elements in the same intervention.